The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.21826/2446-8231201772202
|View full text |Cite
|
Sign up to set email alerts
|

Resposta fisiológica de sementes de chia e linhaça ao estresse hídrico

Abstract: RESUMO -Estudos sobre relações hídricas são importantes para o conhecimento da germinação das sementes. O objetivo deste estudo foi avaliar a resposta fi siológica (germinação) das sementes de chia e linhaça ao estresse hídrico. As sementes foram colocadas sobre papel embebido em solução aquosa de polietileno glicol em diferentes potenciais osmóticos. Foram avaliados a percentagem de germinação, primeira contagem e índice de velocidade de germinação. A redução do potencial osmótico do substrato promoveu decrés… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The reduction in germination due to the increase in water deficit caused by salt stress at -0.4 MPa was also observed in melon seeds by Pinheiro et al (2017). On the other hand, seeds of chia (Salvia hispânica L.) and sesame (Sesamum indicum L.) do not tolerate osmotic potentials of less than -0.15 and -0.2 MPa, respectively (Medeiros et al, 2015;Stefanello et al, 2017).…”
Section: Resultsmentioning
confidence: 80%
“…The reduction in germination due to the increase in water deficit caused by salt stress at -0.4 MPa was also observed in melon seeds by Pinheiro et al (2017). On the other hand, seeds of chia (Salvia hispânica L.) and sesame (Sesamum indicum L.) do not tolerate osmotic potentials of less than -0.15 and -0.2 MPa, respectively (Medeiros et al, 2015;Stefanello et al, 2017).…”
Section: Resultsmentioning
confidence: 80%
“…The reduction of germination due to the increase in water deficit was also verified in melon seeds by Pinheiro et al (2017), who observed germination close to 50% at the potential of -0.4 MPa. By contrast, chia and sesame seeds do not tolerate osmotic potentials lower than -0.15 and -0.2 MPa, respectively (Medeiros et al, 2015;Stefanello et al, 2017).…”
Section: Cmentioning
confidence: 93%